Does Caning Contribute to Criminal Law Enforcement? A Case Study of Aceh, Indonesia - ., Muntoha; Maulida Fitri, Sheila (KnE Social Sciences, 2023)
Since the beginning of the reform era, the Qanun jinayat has been incorporated into the Indonesian constitutional system. However, its application is reaping benefits and drawbacks in policy and practice, where caning is used as a logical result of the Qanun jinayat. This study aimed to reaffirm the background of the legislation of Qanun in Aceh Province and its place within the Indonesian constitutional framework. Additionally, we investigated the applicability of the concept of caning as a substitute for punishment in the context of updating the national criminal code. A normative juridical research methodology was used, comprising a statutory, analytical, and comparative study approach. According to the interpretation of Article 7 of Law Number 12 of 2011 on the Formation of Legislation, the findings of this study showed that the role of Qanun in the Indonesian constitutional system was equivalent to regional laws. In addition, caning is viewed as an alternative to punishment in the context of amending the country’s criminal code by considering the theoretical features of punishment, its intent, the cost-benefit analysis, and its efficacy. Keywords: Qanun, Caning, Criminal Law Reform